MEASURING PERFORMANCE IN PUBLIC AND NONPROFIT ORGANIZATIONS - Theodore H. Poister (Jossey-Bass, 2003)
P erformance measurement has really taken hold in government over the past several years, and over the past few years in the nonprofit sector as well. Although the idea has been around for some time, interest in performance measurement has been reinvigorated in public and nonprofit agencies in recent years as a result of the convergence of two forces: (1) increased demands for accountability on the part of governing bodies, the media, and the public in general, and (2) a growing commitment on the part of managers and agencies to focus on results and to work deliberately to strengthen performance. This shared commitment to both increased accountability and improved performance is embodied in the Government Performance and Results Act of 1993 at the federal level and similar results-oriented legislation in most state governments and some local jurisdictions as well.